Planning of the automatic telephone using radio 450 (ATUR 450) network expansion / Adnan Omar and Shamsul Md. Rasid - Omar, Adnan; Md. Rasid, Shamsul (1992)
Public land mobile radio telephones were first introduced in Malaysia in 1964 with the commissioning of one Master Station at Bukit Besi in Kuala Lumpur. This single base station was only capable of offering service to residents of Kuala Lumpur and adjoining areas. Calls were setup via operators and the subscribers could communicate with subscribers in the wire line network. Automatic service was introduced in 1976 with the KARFON system. Coverage was extended beyond the Kuala Lumpur area and included a major portion of the State of Selangor. The network operated in the VHP band from a single base station at Bukit Besi and comprised three sub-networks with a total of 20 radio channels. While it was more popular than the first mobile telephone system, the limited service area and number of radio channels restricted its capacity to below 500 subscribers. A peak of 483 was reached in 1984 but subsequently the figure dropped slowly after the introduction of the Automatic Telephone Using Radio (ATUR) system.